2020
DOI: 10.1016/j.omtn.2020.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Shuttled circSHOC2 from IPASs Regulates Neuronal Autophagy and Ameliorates Ischemic Brain Injury via the miR-7670-3p/SIRT1 Axis

Abstract: The aim of the present study was to investigate the neuroprotective roles and mechanisms of the circular RNA circSHOC2 in ischemic-preconditioned astrocyte-derived exosomes (IPAS-EXOs) against ischemic stroke. We established an ischemia model based on oxygen glucose deprivation (OGD) in vitro and isolated resultant exosomes from astrocytes. Neuronal viability and apoptosis were determined by Cell Counting Kit-8 (CCK-8) assays and TUNEL (terminal deoxynucleotidyltransferase-mediated deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 42 publications
0
69
0
Order By: Relevance
“…Recent studies have shown that abnormally expressed circRNAs may be involved in the pathogenesis of neonatal HIBD [ 48 ]. Furthermore, exosome-shuttled circRNAs have been shown to improve ischemic brain injury [ 49 ]. Therefore, it is worthwhile to investigate which circRNAs in MSC-exos inhibit microglial pyroptosis and ameliorate neuronal damage by regulating FOXO3a in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that abnormally expressed circRNAs may be involved in the pathogenesis of neonatal HIBD [ 48 ]. Furthermore, exosome-shuttled circRNAs have been shown to improve ischemic brain injury [ 49 ]. Therefore, it is worthwhile to investigate which circRNAs in MSC-exos inhibit microglial pyroptosis and ameliorate neuronal damage by regulating FOXO3a in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA (circRNA) have covalently connected 5′ and 3′ terminal ends, creating a closed long non-coding RNA (lncRNA) [ 151 ]. CircSHOC2, a circRNA transcribed from the SHOC2 gene, delivered in exosomes suppressed apoptosis and ameliorated neuronal damage in an ischemic stroke model by acting through the miR-7670-3p/SIRT1 pathway to regulate autophagy [ 152 ]. In this study, ischemic-preconditioned astrocyte-derived exosomes (IPAS-Exo) were used, as these exosomes were found to have significantly increased levels of CircSHOC2 caused by ischemic treatment.…”
Section: Extracellular Vesicles As Delivery Vehicles To the Cnsmentioning
confidence: 99%
“…Although excessive or insufficient levels of autophagy promote cell death, moderate levels are pro-survival in response to stressful circumstances [ 61 ]. Chen et al demonstrated that exosome-shuttled circSHOC2, a circular RNA from ischemic pre-conditioned astrocytes, reduces neuronal apoptosis by targeting the miR-7670-3p/sirtuin 1 (SIRT1) axis to promote autophagy [ 62 ]. Other As-Exo-derived miRs with similar effects are miR-361 and miR-34c.…”
Section: Preclinical Studies Of Exosomes Derived From Nvu Componentsmentioning
confidence: 99%